Hybrid phishing detection using joint visual and textual identity - Colin Tan Choon, Lin; Chiew, Kang Leng; Kelvin Yong, S. C.; Yakub, Sebastian; Joel Than Chia, Ming; Tiong, Wei King (Elsevier Science, Ltd., 2023)
In recent years, phishing attacks have evolved considerably, causing existing adversarial features that were widely utilised for detecting phishing websites to become less discriminative. These developments have fuelled growing interests among security researchers towards an anti-phishing strategy known as the identity-based detection technique. Identity-based detection techniques have consistently achieved high true positive rates in a rapidly changing phishing landscape, owing to its capitalisation on fundamental brand identity relations that are inherent in most legitimate webpages. However, existing identity-based techniques often suffer higher false positive rates due to complexities and challenges in establishing the webpage’s brand identity. To close the existing performance gap, this paper proposes a new hybrid identity-based phishing detection technique that leverages webpage visual and textual identity. Extending earlier anti-phishing work based on the website logo as visual identity, our method incorporates novel image features that mimic human vision to enhance the logo detection accuracy. The proposed hybrid technique integrates the visual identity with a textual identity, namely, brand-specific keywords derived from the webpage content using textual analysis methods. We empirically demonstrated on multiple benchmark datasets that this joint visual-textual identity detection approach significantly improves phishing detection performance with an overall accuracy of 98.6%. Benchmarking results against an existing technique showed comparable true positive rates and a reduction of up to 3.4% in false positive rates, thus affirming our objective of reducing the misclassification of legitimate webpages without sacrificing the phishing detection performance. The proposed hybrid identitybased technique is proven to be a significant and practical contribution that will enrich the anti-phishing community with improved defence strategies against rapidly evolving phishing schemes.